TOURISM AND INTERNATIONAL RELATIONS. FACTORIES THAT INFLUENCE TO THEM TOURISM INDUSTRY PROMOTION - Teshaboyeva Nafisa Zubaydulla qizi,; Aliyeva Saida Aziz qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation This article analyzes the complex relationship between tourism and international relations.  It  examines  the  role  of  diplomacy,  political  stability,  economic  factors, cultural exchange, and technological advancements in promoting the tourism industry. The  study  also  explores  how  globalization  and  the  concept  of  soft  power  allow countries  to  enhance  their  international  image  and  attract  more  tourists.  Practical examples  and  policy  recommendations  for  sustainable  tourism  development  are provided.